Avaliação da microdureza superficial de resinas compostas extraclaras fotopolimerizadas por luz halógenas e LEDs. descrição das caracteristícas dos aparelhos fotopomerizadores - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2004)
DELGADO, L. Evaluation of the superficial microhardness of extra-light composite resins photocured by Halogen Light and LEDs. Description the characteristics of the light sources. Ponta Grossa, 2004. 129 Dissertação (Mestrado em Clínica Integrada) – Faculdade de Odontologia, Universidade Estadual de Ponta Grossa. The purpose of this study was to evaluate the superficial microhardness of four extralight microhibrid composite resins photocured with different types of light curing units: Halogen and LEDs. The emission spectrum (nm) and power (mW) of the curing units were tested using the spectrometer USB2000 (Ocean Optics) and the Power Meter (Ophir). The light intensity (mW/cm2) was determined through the value of power and area the light guide of each unit (i=P/A). The resins and colors used were: Tetric® Ceram (Ivoclar Vivadent) A2 and XL; FiltekTM Z250 (3M-ESPE) A2 and B0.5; Charisma® (Heraeus Kulzer) A2 and SL; and Esthet X (Dentsply) A2 and XL. The curing units used were: Curing Light 2500 (3M-ESPE) and Elipar® FreeLight (3MESPE). Metallic matrixes were made with a hole of 5mm diameter and 2 mm thick. Samples of the resins were made on these matrixes and were marked and storaged in dry, dark jars for 24 hours. After this, the samples were evaluated using Vickers microhardness test through the digital microhardmeter MMT-3 (Buehler) with 50 gf charge for 30 seconds. Data collected was analyzed with a mutlifactorial variance and Tukey tests. T-test was used on paired samples to determine significant difference between surfaces. Also was calculated the percentage of depth of cure. Results showed that the emission spectrum of the LED curing unit was more reduced than the halogen curing unit (430–520nm and 400-520nm respectively). Nevertheless, the halogen curing unit presented a greater power and intensity of light. The factors analyzed (type of resin, color and light source) influenced the microhardness values. It was found that the extra-light color resins presented the least values of microhardness independent to the light source. The LEDs curing units presented the least values of superficial microhardness. The Tetric® Ceram XL resin composite showed percentage of depth of cure less 80%, independent to the light source. The same occurred with A2 and XL colors the Charisma® resin composite when cured with LEDs unit.
Keywords: dureza; resina composta; cor; hardness; composite resin; color; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA